The cause of human action according to Alexander of Aphrodisias, Mantissa 23 and De Fato 15 - Natali, Carlo (Estudios de Filosofía, 2009)
Carlo Natali’s essay is concerned with closely examining Alexander’s debate with the determinists as well as his reasons to show the crucial role of deliberation in the account of action. Alexander’s starting point is chapter 9 of De interpretatione, text that indicates that Aristotle clearly envisaged the consequences, absurd in his view, of determinism. In his discussion, Natali examines the in uence of Alexander’s arguments on Boetius’commentary on De interpretatione; an aspect particularly remarkable of Natali’s essay is that he shows that Alexander –and previously Aspasius–, even taking for granted the assumed crucial relevance of deliberation in the account of action, modifies in part the Aristotelian theory of deliberation, since he attempts to adapt it to the new cultural situation and the new philosophical debate of his time. Natali notes that Alexander’s apparent incorporation of Stoic terminology and notions (such as that of assent) is part of a clever strategy to fight against the Stoic determinists in their own ground: the crucial point is the deliberation as a central ingredient in the explanation of action, as well as the fact that one is able to choose a thing or something different from it (De fato 178, 22), if that appears preferable.